Large Bank Failures and Investor Risk Perceptions: Evidence from the Debt Market - Fraser, Donald R.; McCormack, J. Patrick (Journal of Financial and Quantitative Analysis, 1978)
The commercial banking industry has been buffeted by a variety of forces in recent years. Alternating periods of intense monetary restraint and the severity of the 1973–74 economic contraction (especially as it affected the real estate industry), huge losses on loan portfolios, a heavy commitment of funds to less developed countries on the part of a few major banks, and the failures of a number of individual banks have created considerable discussion about the stability of the banking system. Questions have been raised about the risk involved in committing funds to the securities of banking organizations. Moreover, the importance of these questions has been underscored for bank management by the necessity for many banking organizations to raise substantial amounts of external funds to prevent further depletion of existing capital ratios.